Renal Impairment Associated with Autoinflammatory Diseases - JIAN Shan; WANG Changyan; ZHANG Caihui; SONG Hongmei (罕见病研究)
Kidney is one of the key target organs involved in autoinflammatory diseases (AIDs). The clinical manifestations of renal impairment associated with AIDs are diverse, including hematuria, proteinuria, nephrotic syndrome, hypertension, renal artery stenosis, renal insufficiency, and others. The pathogenesis is mostly renal amyloidosis and/or renal vasculitis/vasculopathy caused by inflammasome activation. Whether or not the kidney is involved and its degree is closely related to the prognosis of AIDs patients. This article introduces the pathogenesis of AIDs-related renal impairmen and highlights the clinical characteristics of renal damage in some AIDs, aiming to enhance clinicians′ understanding of AIDs-related renal damage, and to implement early diagnosis and treatment to improve patients′ quality of life and prognosis.